(untitled) (Comunicação & Inovação, 2022)
The objective of this article is to explain the omissions of information and ethical slips of the journalist Joseph Mitchell in the making of the two profiles of the bohemian Joe Gould. The approach uses the comparative method and concepts of journalistic ethics, narrative analysis and linguistics. With these procedures and contributions, we demonstrate that, contrary to being models for the genre, due to their celebrated quality, Joe Gould’s two profiles are examples of what should be avoided when writing biographical journalistic texts.